Sustainable Development in Light of Research by Scientists from Poland, Czechia and Slovakia. Different Research Perspectives [całość] - Drelich-Skulska, Bogusława. Redakcja; Sobocińska, Magdalena. Redakcja; Tomášková, Andrea. Redakcja (Publishing House of Wroclaw University of Economics and Business, 2025)
The multidimensionality of the concepts of sustainable development is shown in this monograph through the prism of literature reviews and empirical studies, as well as experiences of 30 authors representing 13 universities and science institutes. The monograph confirms the long-standing academic cooperation between the research community of Wroclaw University of Economics and Business and other academic centres in Poland with scholars from Czechia and Slovakia. It is also worth noting that the list of the contributors has been further extended to authors from Hungary and Pakistan who are part of international research teams working in Poland and Czechia. The main structure of the monograph is composed of four parts. Part 1 concentrates on tasks which institutions of higher education have to realise in the context of expanding the scope of implementing the principles of sustainable development. The considerations in Part 2 are directed at the regional dimension of sustainable development, with particular attention to its economic aspects demonstrated in the context of regions. The authors of the chapters in Part 3 indicate the importance of technological advancements and the possibility of their use to support sustainable development, whilst Part 4 presents the issues linked with sustainable development from the perspective of consumer behaviour and business activity of enterprises. [author's note]
Quote as: Drelich-Skulska, B., Sobocińska, M., & Tomášková, A. (Eds.). (2025). Sustainable Development in Light of Research by Scientists from Poland, Czechia and Slovakia. Different Research Perspectives. Publishing House of Wroclaw University of Economics and Business.
s. 260
Publikacja dostępna wyłącznie na terenie kampusu Uniwersytetu Ekonomicznego we Wrocławiu.
Copyright notice is valid until 30 June 2026. Since 1 July 2026 the publication is available under Creative Commons Attribution-ShareAlike 4.0 International License (CC BY-SA 4.0).
Keywords: sustainable development; higher education institutions; technological advancements; green transformation; changes in consumer behavior